2012
DOI: 10.1309/ajcpifhparjej69n
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 Expression Patterns in Microscopic Colitides

Abstract: Microscopic colitides, including lymphocytic (LC) and collagenous colitis (CC), are well-described pathologic conditions. An altered immune response is implicated in the pathogenesis of both entities. CD8+ T lymphocytes (CTLs) secrete interleukin 2 which stimulates proliferation of regulatory T cells (Tregs), and Tregs, in turn, inhibit CTLs, inducing cytotoxic tissue damage. In Tregs, Foxp3 regulates T-cell-related immune responses. The distribution of Tregs and CTLs in microscopic colitides has remained unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…While there are several specific histological differences that distinguish lymphocytic colitis from collagenous colitis, both entities have a considerable clinical and therapeutic overlap . It is still unclear whether collagenous colitis and lymphocytic colitis should be considered two distinct entities or different subtypes of the same disease, since recent research has identified differences in the pathological mechanisms underlying the development and maintenance of the two subtypes, albeit in a common pathogenetic context …”
Section: Discussionmentioning
confidence: 99%
“…While there are several specific histological differences that distinguish lymphocytic colitis from collagenous colitis, both entities have a considerable clinical and therapeutic overlap . It is still unclear whether collagenous colitis and lymphocytic colitis should be considered two distinct entities or different subtypes of the same disease, since recent research has identified differences in the pathological mechanisms underlying the development and maintenance of the two subtypes, albeit in a common pathogenetic context …”
Section: Discussionmentioning
confidence: 99%
“…in nine of 65 (14%) patients: three from collagenous to lymphocytic colitis, and six from lymphocytic to collagenous colitis. In another report, two patients were diagnosed with lymphocytic colitis at the beginning of the study, but were found to have collagenous colitis on later follow‐up biopsies . These data, however, need to be confirmed in further studies, as the overlap of histological features together with the patchy, non‐uniform distribution of both diseases along the colon might lead to an erroneous assumption of true conversion if the number of sampled biopsies is small.…”
Section: Microscopic Colitis: a Spectrum Of Diseases?mentioning
confidence: 93%
“…The notion of a histological overlap between lymphocytic and collagenous colitis and the rare occurrence of disease conversion caused some authors to conclude that lymphocytic and collagenous colitis are in fact two histological manifestations of the same disease entity, possibly representing different manifestations during the disease course or different stages of disease development . This hypothesis is, however, still lacking further evidence, in particular experimental evidence, and a definitive conclusion cannot be drawn.…”
Section: Microscopic Colitis: a Spectrum Of Diseases?mentioning
confidence: 99%
“…About 60% of the CD4 + LPL were GATA-3 + [144] pointing to Th2 cells activated by TCR dependent or independent of the IL-4 receptor [146]. Treg counts are more increased in collagenous than in lymphocytic colitis [147]. In patients initially diagnosed with lymphocytic colitis that later developed collagenous colitis, overall IEL numbers dropped while Treg counts increased [147].…”
Section: Microscopic Colitismentioning
confidence: 99%
“…Treg counts are more increased in collagenous than in lymphocytic colitis [147]. In patients initially diagnosed with lymphocytic colitis that later developed collagenous colitis, overall IEL numbers dropped while Treg counts increased [147]. …”
Section: Microscopic Colitismentioning
confidence: 99%